2018
DOI: 10.3389/fimmu.2018.00599
|View full text |Cite
|
Sign up to set email alerts
|

Human Vγ9Vδ2-T Cells Synergize CD4+ T Follicular Helper Cells to Produce Influenza Virus-Specific Antibody

Abstract: Human Vγ9Vδ2-T cells recognize nonpeptidic antigens and exert effector functions against microorganisms and tumors, but little is known about their roles in humoral immune response against influenza virus infection. Herein, in the coculture of autologous human B cells, dendritic cells and/or naïve CD4 T cells, and Vγ9Vδ2-T cells, we demonstrated that Vγ9Vδ2-T cells could facilitate H9N2 influenza virus-specific IgG and IgM productions in a CD4 T cell-dependent manner. Vγ9Vδ2-T cells promoted the differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, γδ T cell expression of CD16, which is known to mediate antibody-dependent cellular cytotoxicity (ADCC) in CMV infection ( 24 ) is increased in children in malaria-endemic regions ( 34 , 35 ), suggesting a potential role for γδ T cells in inciting antibody-mediated parasite killing (Figure 1 ). Finally, paralleling previous observations during influenza infection ( 98 ), recent work in the P. berghei mouse model demonstrated a role for γδ T cells in increasing levels of antigen-specific antibodies, Tfh cells, and germinal center B cells via expression of IL-21 and IFNγ early in infection ( 54 ). Altogether, evidence suggests that malaria-responsive γδ T cells are able to use diverse direct and indirect (via recruitment of monocytes, dendritic cells, and CD4+ cells) mechanisms to influence effector responses later in infection.…”
Section: γδ T Cell Roles In Stimulating Other Innate and Adaptive Immsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, γδ T cell expression of CD16, which is known to mediate antibody-dependent cellular cytotoxicity (ADCC) in CMV infection ( 24 ) is increased in children in malaria-endemic regions ( 34 , 35 ), suggesting a potential role for γδ T cells in inciting antibody-mediated parasite killing (Figure 1 ). Finally, paralleling previous observations during influenza infection ( 98 ), recent work in the P. berghei mouse model demonstrated a role for γδ T cells in increasing levels of antigen-specific antibodies, Tfh cells, and germinal center B cells via expression of IL-21 and IFNγ early in infection ( 54 ). Altogether, evidence suggests that malaria-responsive γδ T cells are able to use diverse direct and indirect (via recruitment of monocytes, dendritic cells, and CD4+ cells) mechanisms to influence effector responses later in infection.…”
Section: γδ T Cell Roles In Stimulating Other Innate and Adaptive Immsupporting
confidence: 78%
“…In addition, inflammation during recurrent malaria leads to suppression of functional memory B cells (MBC) ( 111 ) and expansion of “inferior” T follicular helper (Tfh) cells ( 112 , 113 ) and “atypical” MBC exhibiting impaired proliferation, cytokine production and antibody secretion ( 114 ). Considering the overlapping timing of immunoregulatory phenotypes developing in γδ T cells and adaptive cells, as well as evidence for γδ T cells impacting germinal center reactions in murine malaria ( 54 ) and Tfh differentiation during influenza ( 98 ), future research should examine the impact of altered γδ T cell function on expansion of MBC and Tfh subsets and interactions with other immune cells.…”
Section: Directions For Future Research and Application To Potential mentioning
confidence: 99%
“…37 This study showed that human cd T cells promote Tfh-cell differentiation, resulting in the induction of plasma cell differentiation and B-cell immunoglobulin class switching. 37 This study showed that human cd T cells promote Tfh-cell differentiation, resulting in the induction of plasma cell differentiation and B-cell immunoglobulin class switching.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study reported that human Vc9 + Vd2 + cd T cells, a major cd T-cell subset in humans, facilitated H9N2 influenza virus-specific IgG production. 37 This study showed that human cd T cells promote Tfh-cell differentiation, resulting in the induction of plasma cell differentiation and B-cell immunoglobulin class switching. Moreover, they observed that human cd T cells induced CD4 T cells to produce IL-21 and IL-13, resulting in enhanced plasma cell differentiation.…”
Section: Discussionmentioning
confidence: 92%
“…79 Phosphoantigenactivated cells also have non-cytolytic activities in response to pandemic H1N1, producing IFNc and expressing inflammatory chemokines. 80 Relatedly, it was also recently shown that Vc9Vd2 T cells can promote CD4 + T follicular helper cell differentiation, B-cell class switching and influenza virus-specific antibody production in an in vitro co-culture assay, 81 suggesting that these cells may provide both a direct cytotoxic and potential synergistic role in the adaptive immune response to influenza.…”
Section: Viral Infectionsmentioning
confidence: 94%